The Assistance of Social Services in Toba Regency towards Child Victims of Sexual Violence - Eleven Sihotang; Sari Asi Situmorang (Jurnal Sosiologi Nusantara, 2025)
This study discusses the assistance provided by the Social Services in Toba Regency to children who are victims of sexual violence. Toba Regency was chosen because of the increasing number of sexual violence cases, which has even been referred to as a red zone. The research technique in this review is a qualitative research method with a descriptive type. Based on field data, several causes of sexual violence were found and tended to be due to pornography and low economic status. The perpetrators stated that the freedom to access sexual videos or photos led them to practice it directly, targeting children. This is because children cannot fight back and refuse the requests of the adults who are the perpetrators. Meanwhile, low economic factors cause parents (mothers) to work outside the home more often as farmers, while fathers stay at home. Such circumstances also result in perpetrators of sexual violence being parents and close family members. In light of this situation, the Social Service in Toba Regency strives to provide assistance to victims and their families in various forms, ranging from visits and strengthening victims to accompanying them to court to prosecute perpetrators.